The Impact of Age Pension Eligibility Age on Retirement and Program Dependence: Evidence from an Australian Experiment - Atalay, Kadir; Barrett, Garry F. (The Review of Economics and Statistics, 2015)
Governments around the world are reforming their social security systems in light of the challenges posed by population aging. We study the 1993 Australian Age Pension reform, which progressively increased the eligibility age for women from 60 to 65 years. We find economically significant responses to the reform. An increase in the eligibility age of one year induced a decline in the probability of retirement by 12 to 19 percentage points. In addition, the reform induced significant program substitution, with increases in enrollment in other social insurance programs, particularly the disability support pension, which effectively functioned as an alternative source of retirement income.